Obesity markers for the prediction of incident type 2 diabetes mellitus in resource-poor settings: The CRONICAS Cohort Study - Zafra-Tanaka J.H. (2020)
Aims: To determine the predictive performance of well-known obesity markers: body mass index (BMI), waist circumference (WC), waist-hip ratio (WHR), waist-height ratio (WHtR), and total body fat percentage (TBF%), to identify incident cases of type 2 diabetes mellitus T2DM. Methods: Secondary data analysis of the CRONICAS Cohort Study, conducted in 3 regions of Peru. Participants without T2DM at baseline were selected for analyses. The obesity markers were evaluated at the beginning of the study, and the development of T2DM was determined at 30 months of follow-up. The predictive performance of the markers was calculated using areas under the curve (AUC), and sensitivity and specificity of the best cutoff points were estimated. Results: A total of 2510 participants with no diabetes at baseline, median age 54.1 years (inter-quartile range: 44.6 to 63.5), were included in the analysis. The cumulative incidence of T2DM at 30 months of follow-up was 4.7%. All the AUC studied for obesity markers and TBF% were poor. Conclusions: We found that obesity markers had a poor predictive performance (AUC) for the incidence of T2DM when used alone. The BMI, WC and WHtR had better performance for the incidence of T2DM relative to the WHR among women, and no differences in performance between obesity markers were found among men. © 2020 Elsevier B.V.